A cardiogenic shock in PICU turned out to be a bilateral pheochromocytoma: A case report - Jay Shah; Zinkal Patel; Shradha Patel; Amit Kumar (Wolters Kluwer Medknow Publications, 2021)
Pheochromocytomas (PCCs) are rare catecholamine-secreting tumors arising from adrenomedullary chromaffin cells, usually causing hypertension, palpitation, and headache. It is usually investigated as a secondary cause of hypertension. However, rarely it can present in hypotension. In "PCC crisis," the patient presents with hypotension, multiple organ dysfunction, leaving the physician with diagnostic difficulties. In this case, we present an adolescent male presented with hypotensive cardiogenic shock, and multiple organ dysfunction on admission, which during investigation turned out to be bilateral PCC.